DNA damage and circulating cell free DNA in greenhouse workers exposed to pesticides. (11th November 2017) - Çayir, Akin; Coskun, Mahmut; Coskun, Munevver; Cobanoglu, Hayal
Abstract : Pesticides widely used in agriculture and other applications have been linked to cancer and other diseases through several potential mechanisms. The goals of this study were to assess DNA damage in lymphocytes by the cytokinesis‐block micronucleus assay (CBMN), and to measure circulating cell free DNA (ccf‐DNA) in the blood of pesticide‐exposed greenhouse workers and matched controls living in the same area. CBMN was applied to peripheral blood lymphocyte samples taken at different times (spring and autumn) for each individual. We measured plasma ccf‐DNA levels using a Qubit ® fluorometer. The results indicated that the MNL, BNMN, and NBUDs frequencies of pesticide‐exposed individuals were significantly higher than non‐exposed individuals. Apart from MNL, BNMN and CBPI, a season‐related effect was found for the NPB and NBUD frequencies. With MNL and BNMN as the dependent variables, multiple regression analysis showed that age and gender affected MN formation. The ccf‐DNA level in the pesticide‐exposed group was significantly higher than the control group. There was no seasonal variation regarding the free DNA amount. Ccf‐DNA in males was found to be higher than females. The MNL, BNMN, NPB, and CBPI did not correlate with the ccf‐DNA amount. It can be concluded that pesticide exposure can modulate DNA integrity via different mechanisms. Also, elevated levels of ccf‐DNA could be recommended as a biomarker of pesticide exposure. Environ. Mol. Mutagen. 59:161–169, 2018. © 2017 Wiley Periodicals, Inc.